2011
DOI: 10.1097/bor.0b013e328344a732
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with biologics of pregnant patients with rheumatic diseases

Abstract: Differences in molecular structure of TNFα inhibitors may turn out to favor the use of agents that are not complete monoclonal antibodies in women who consider pregnancy. The very limited experience with abatacept, tocilizumab or anakinra in pregnancy allows no statement as to their compatibility with pregnancy. At present use of biological agents throughout pregnancy cannot be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 30 publications
0
22
0
7
Order By: Relevance
“…To date, studies of children who were exposed to rituximab early in pregnancy have not demonstrated any adverse outcomes. By contrast, second-and third-trimester exposure causes B-cell depletion in the fetus with unknown long-term effects [100]. Although few congenital malformations or neonatal infections were seen among exposed neonates, women should continue to be counseled to avoid pregnancy for 6-12 months after rituximab exposure [101,102].…”
Section: Therapy Of Lupus Flares During Pregnancymentioning
confidence: 99%
“…To date, studies of children who were exposed to rituximab early in pregnancy have not demonstrated any adverse outcomes. By contrast, second-and third-trimester exposure causes B-cell depletion in the fetus with unknown long-term effects [100]. Although few congenital malformations or neonatal infections were seen among exposed neonates, women should continue to be counseled to avoid pregnancy for 6-12 months after rituximab exposure [101,102].…”
Section: Therapy Of Lupus Flares During Pregnancymentioning
confidence: 99%
“…Tabell 1 viser de mest brukte medikamentene for artrittsykdom og råd om bruk under svangerskap (44,46,47).…”
Section: Svangerskapetunclassified
“…Dyrestudier og data fra human eksponering i svangerskap tyder ikke på økt risiko for misdannelser hos fosteret (46,47), men erfaringen er fortsatt begrenset.…”
Section: Svangerskapetunclassified
See 2 more Smart Citations